Enhancing Government Effectiveness and Transparency : The Fight Against Corruption - World Bank (World Bank, Kuala Lumpur, 2020)
News headlines over the last few years have been filled with global scandals involving corruption on an unprecedented scale. They touch virtuallyevery continent, from Asia to Africa, Europe, and the Americas. The scale, magnitude, and sophistication of the operations has increasingly risen to levels that many had not considered possible before. Governments are forever in search of new approaches and tools that can help identify loopholes and entry points for corrupt activities. While the containment of COVID-19 (coronavirus) and its devastating human and economic impacts have more recently been the focus of government actions, it is almost certain that huge amounts of spending in a short time, circumventing the standard operating procedures, will result in new corruption scandals in the post-COVID (coronavirus) years. There are already reports in papers regarding inflated food prices or favored medical contracts to firms from a few countries. In drawing on the past and looking ahead to the future, the time is ripe for the World Bank to take a fresh look at the state of play in tackling corruption and how countries are attempting to address this long-standing scourge on development.